2000
DOI: 10.1002/1096-9071(200012)62:4<518::aid-jmv18>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced detection of respiratory syncytial virus by shell vial in children hospitalised with respiratory illnesses in Northern Jordan

Abstract: During the period between November 1997 and May 1998, a total of 350 nasopharyngeal aspirates were obtained from children admitted to the Respiratory Disease Unit at Princess Rahma Hospital, northern Jordan, and diagnosed clinically as suffering from respiratory tract infections. Nasopharyngeal aspirates were investigated for the presence of respiratory syncycial virus (RSV) by using shell vial (SV) culture assay, conventional culture assay, and direct immunofluorescence assay. Out of 350 nasopharyngeal aspira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
1
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
3
8
1
1
Order By: Relevance
“…Fully 89.4% of the hospitalized Jordanian infants in this study were <1 y of age and 1 of 4 children had an underlying medical condition. The median age of 3.6 months in our cohort is consistent with other studies worldwide documenting RSV hospitalization in young infants [8,21,22]. In the USA, 66% of the children hospitalized with RSV at 3 major hospitals were young, previously healthy children [23].…”
Section: Discussionsupporting
confidence: 89%
“…Fully 89.4% of the hospitalized Jordanian infants in this study were <1 y of age and 1 of 4 children had an underlying medical condition. The median age of 3.6 months in our cohort is consistent with other studies worldwide documenting RSV hospitalization in young infants [8,21,22]. In the USA, 66% of the children hospitalized with RSV at 3 major hospitals were young, previously healthy children [23].…”
Section: Discussionsupporting
confidence: 89%
“…In our 2010-2013 surveillance window, RSV was a major cause of ARI hospitalizations in Jordanian children <2 years, with consistent annual peaks in January and February. Our study represents one of the largest cohort studies of RSV-infected hospitalized children, including within the Middle East [10][11][12][13][34][35][36][37][38][39][40][41][42][43]. RSV is well-recognized cause of ARI globally [2], but even comprehensive reports typically fail to include information from the Middle East region due to lack of published data.…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained here were similar to those observed in other countries, and supports the hypothesis that viruses are the most frequent pathogen involved in respiratory diseases in children and immunocompromised patients worldwide. 4,[6][7][8][9][10][11][12]17,19 RSV is associated with high rates of morbidity and mortality in transplant recipients and consistently represents one of the leading two causes of respiratory viral infections in this population. 7 According to the results obtained in our study, the same situation was observed in BMT and also in paediatric patients, especially children from ICU.…”
Section: Discussionmentioning
confidence: 99%
“…The samples were processed within 4 h after collection to investigate the presence of RSV, FLUA, FLUB, ADENO, and PIV by IFA 5,7,23 and SV (Shell Vial Culture). 11,12,15,17 Detection of viruses in cells shed by the respiratory tract or from inoculated lineages harvested from cell culture tubes was performed by IF as previously described, 4,6,19 using commercially available monoclonal antibodies (Chemicon International Inc., Temecula, CA).…”
Section: Methodsmentioning
confidence: 99%